Assessment of yield and adaptive properties of winter wheat varieties in the Udmurt Republic conditions - A. G. Kuryleva (Аграрная наука Евро-Северо-Востока)
In various soil and climatic conditions of the Udmurt Republic, according to yield data (2016-2018) of state variety testing plots (GSU), ecological plasticity, stress resistance, genetic flexibility of 10 zoned and new varieties of winter wheat (standard - Volzhskaya K) were evaluated. The soil of the state variety testing sites: soddy-telopodzol sandy loamy - Uvinsky state varietal test site; light-gray forest heavy loamy - Sarapulsky state varietal test site; sod-mid-podzolic medium loamy - Mozhginsky state varietal test site. The agrometeorological conditions of the growing seasons differed in terms of heat and moisture supply: 2016 - hot and dry (hydrothermic coefficient – 0.70), 2017 - excessively humid (hydrothermic coefficient – 2.14), 2018 - wet (hydrothermic coefficient – 1.21). A high yield of winter wheat varieties was revealed in the southern zone of the Udmurt Republic (Sarapulskiy GSU - 3.32 t/ha and Mozhginskiy GSU - 2.95 t/ha). Weather conditions of the year mostly influenced the formation of winter wheat yield - 64.8-98.5 %. The share of participation of the variety is 0.8-31.7 %. A relatively high (3.40-3.47 t/ha) "genetic flexibility" of varieties Darina, Mera and Kazanskaya 285 was revealed, 7-9 % higher than the Volzhskaya K standard. The highest level of environmental sustainability was established in the varieties Volzhskaya K and Mera ‒ d = 67.36-67.44 %. According to the indicators of plasticity, a strong response to changes in environmental conditions was revealed in Darina, Mera, Universiada varieties (bi = 1.05-1.09); weak reaction – in Biryuza and Ilot varieties (bi = 0.91-0.92); plastic varieties - Volzhskaya K, Bashkirskaya 10, Italmas, Kazanskaya 285 and Moskovskaya 39 (bi = 0.96-1.01). The smallest gap between the maximum and the minimum yield (stress resistance) was noted for the Ilot variety ‒ 2.91 t/ha.